5-Alkyl-8-hydroxyquinolines: Synthesis and Application in Dye-Sensitized Solar Cells - Manthou, Victoria S.; Perganti, Dorothea; Rotas, Georgios; Falaras, Polycarpos; Vougioukalakis, Georgios C. (Synlett, 2017)
The use of co-adsorbents in dye-sensitized solar cells (DSCs) increases both the power-conversion efficiency and long-term stability of these devices. Co-adsorbents usually consist of a hydrophobic moiety attached on a carboxylic or phosphoric acid terminal anchoring group, which chemisorbs on the semiconductor surface. In this work, the synthesis of a new family of 8-quinolinol derivatives bearing alkyl chains of variable length at the 5-position is described and their comparative efficiency as effective bidentate co-adsorbents in DSCs is evaluated. The key step towards their straightforward modular synthesis is a Suzuki coupling between 5-chloro-8-methoxyquinoline and alkyltrifluoroborates. The new compounds showed better performance as co-adsorbents in terms of cell efficiency as compared to their alkylcarboxylic acid analogues, with the best results obtained from the derivative bearing the longer dodecyl alkyl chain.
Keywords: dye-sensitized solar cells; co-adsorbents; hydroxyquinoline; Suzuki coupling; organotrifluoroborates